Curriculum Development Based on Local Cultural Wisdom at Al Jannah Early Childhood Education Unit Magelang Regency - Wiwiek Sumayni; Yuliantina, Irma (Kirana Publisher (KNPub), 2025)
This study aims to develop a curriculum for the Al Jannah Early Childhood Education (PAUD) unit that can optimize the integration of local cultural wisdom. This study uses the Four-D model where this model can be seen as a model for instructional development, namely: 1) Define; 2) Design; 3) Development; 4) Dissemination. The feasibility of the local cultural wisdom-based curriculum development product at the Al Jannah PAUD unit has been tested through expert validation and teacher perception analysis. The validation results from material experts show an average feasibility percentage of 77.22% (category